2020
DOI: 10.7196/samj.2020.v110i3.14403
|View full text |Cite
|
Sign up to set email alerts
|

Medical cannabis: What practitioners need to know

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…Diferentemente, os receptores CB2 são expressos principalmente nos tecidos imunes periféricos, como baço, linfonodos e medula óssea, nas células B, macrófagos e micróglias, onde a ativação pode levar a respostas imunossupressoras. Sua expressão nos neurônios do Sistema Nervoso Central é limitada e inclui o tronco cerebral e hipocampo, onde a ativação pode afetar a excitabilidade neuronal (Gaston & Friedman, 2017;Van Rensburg et al, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Diferentemente, os receptores CB2 são expressos principalmente nos tecidos imunes periféricos, como baço, linfonodos e medula óssea, nas células B, macrófagos e micróglias, onde a ativação pode levar a respostas imunossupressoras. Sua expressão nos neurônios do Sistema Nervoso Central é limitada e inclui o tronco cerebral e hipocampo, onde a ativação pode afetar a excitabilidade neuronal (Gaston & Friedman, 2017;Van Rensburg et al, 2020).…”
Section: Resultsunclassified
“…O CBD desempenha efeito anticonvulsivante significativo no tratamento das síndromes de Lennox-Gastaut e Dravet, em parte por direcionar correntes de sódio ressurgentes em vez de correntes transitórias de pico geradas pelos canais para sódio dependente de voltagem (Nav1.6), bem como a corrente ressurgente e persistente aberrante geradas pelos canais mutantes de Nav1.6 (Devinsky et al, 2017). A terapia adjuvante de canabinoides pode reduzir a frequência de convulsões para a síndrome de Dravet em 22,8% e para a síndrome de Lennox-Gastaut em 18,8%, (Van Rensburg et al, 2020). Outros achados importantes foram a diminuição significativa da frequência de convulsões, melhora no padrão de sono, e melhora cognitiva.…”
Section: Efeitos Antiepilépticosunclassified
“…It has been demonstrated that cannabinoid compounds act on the endocannabinoid system (ECS), via type 1 (CB1) and type 2 (CB2) cannabinoid receptors, their endogenous ligands, and the enzymes responsible for their synthesis and degradation [75]. CB1 receptors are abundant in the brain and CNS, as well as in other tissues, while CB2 receptors are primarily found in immune cells and within the cardiovascular, gastrointestinal, and reproductive systems, where they are thought to regulate several important functions [76]. CB1 and CB2 receptors can be stimulated by endocannabinoids, phytocannabinoids, or synthetic cannabinoids.…”
Section: Role Of Cannabis Compounds In Neurological and Systemic Infl...mentioning
confidence: 99%
“…CB1 and CB2 receptors can be stimulated by endocannabinoids, phytocannabinoids, or synthetic cannabinoids. An important consideration is that the affinities and potencies of different cannabinoids for CB1 and CB2 receptors vary, therefore, the efficacy and safety of one cannabinoid cannot be applied to another [76]. The CB2 receptor, and to a lesser extent the CB1 receptor, have been identified as being involved in regulating the release of proinflammatory mediators and modulation of immune cells [75].…”
Section: Role Of Cannabis Compounds In Neurological and Systemic Infl...mentioning
confidence: 99%